The September issue [videorecording (DVD)] - Cutler, R. J.; Wintour, Anna, 1949-; Coddington, Grace, 1941-; Panichgul, Thakoon, 1974-; Talley, André Leon; Wang, Vera; De la Renta, Oscar (Lionsgate, 2010)
A behind-the-scenes look at Vogue magazine (U.S.) as editor-and-chief Anna Windtour and her staff prepare the September 2007 issue.